PEMANFAATAN TRAS ALAM DARI SAYUTAN MAGETAN DAN KAPUR DARI NGAMPEL BLORA SEBAGAI BAHAN SUBSTITUSI SEMEN UNTUK CAMPURAN MORTAR - , Muhamad Nurzain, Prof. Ir. Iman Satyarno, M.E, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Construction works in the Regency of Magetan, as well as in the mountain area far from capital cities and remote from transpiration facilities, require large amount of material. The District of Parang is one of mountain areas with almost 25-30 km distance to the nearest capital city. In order to cope with the need of sand, people uses natural trass which are plenty to be found in the area. Traditionally, the natural trass has been used by the people to substitute sand for blocks, channels, tiles and mortar for space in clay brick masonry. However, the test and research on its characteristic and strength with its potentials to be used as cement substitution have never been carried out. Trass in this research was taken from three villages in Desa Sayutan, Magetan. Lime was taken from Desa Ngampel, Blora as it is commonly sold in the area and sand was taken from Sungai Gandong, Magetan. The planned mixture of lime-trass paste was in the effort to obtain the best composition. The weight ratios used were 100%:0%, 80%:20%, 60%:40%, 40%:60%, 20%:80 and 0%:100%. The mortar mixture with cement substitution was 100%, 80%, 60%, 40%, 20% and 0%. The types tests for mortar incuded the tests of flow table, compressive strength, tensile strength, water absorbency and weight changing for 28,56 and 90 days of specimens. The tests of trass-lime block were compressive strength and water absorbency for 28 days of specimens. The test results in this study showed that the specific gravity, unit weight, water absorbency of Dukuh trass were 2.703, 1.171 gr/cm 3 and 0.523%, respectively. The specific gravity, unit weight, water absorbency of Jeruk trass were 2.665, 1.051 gr/cm 3 and 0.482%, respectively. The specific gravity, unit weight, water absorbency of Sumber trass were 2.672, 1.089 gr/cm 3 and 0.725%, respectively. The rass specific gravity, unit weight, water absorbency of lime were 2.165, 0.474 gr/cm 3 and 1.283%, respectively. The specific gravity and unit weight of sand were 2.565 and 1.511 gr/cm 3 , respectively. The results of the tests of compressive strength for the lime-trass paste indicated the highest value was achieved at 20% of lime and 80% of trass Sumber. The compressive strength of the lime-trass mixture was between 0.000 MPa and 2.545 MPa. The mortar compressive strength achieved was 0.373 MPa - 26.585 MPa. The test results of mortar compressive strength showed that the more cement substitution amount used, the lessen the compressive strength would be. The same condition occurred in the test of mortar tensile strength. The mortar compressive strength increased in line to the age of the mortar. The mortar tensile strength obtained was 0.000 MPa - 2.169 MPa. The mortar water absorbency in 10 minutes inundation was 4,762% - 11.906% and in 24 hours inundation was 10.899% - 13.702%. The changing of the mortar weight was between 6.170% - 15.823%. The block compressive strength obtained was 3.336 MPa - 3.403 MPa. Water absorbency of the block was 15.831% -16.056%.